2009
DOI: 10.1111/j.1582-4934.2008.00546.x
|View full text |Cite
|
Sign up to set email alerts
|

Intracardiac injection of erythropoietin induces stem cell recruitment and improves cardiac functions in a rat myocardial infarction model

Abstract: Erythropoietin (EPO) protects the myocardium from ischaemic injury and promotes beneficial remodelling. We assessed the therapeutic efficacy of intracardiac EPO injection and EPO-mediated stem cell homing in a rat myocardial infarction (MI) model. Following MI, EPO (3000 U/kg) or saline was delivered by intracardiac injection. Compared to myocardial infarction control group (MIC), EPO significantly improved left ventricular function (n= 11–14, P< 0.05) and decreased right ventricular wall stress (n= 8, P< 0.05… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 53 publications
(69 reference statements)
2
44
0
1
Order By: Relevance
“…Administering EPO to rats immediately after coronary occlusion (5000 IU/kg/day for 7 days) reduced cardiomyocyte loss by 50% (Calvillo et al, 2003). Recently, Klopsch et al (2009) have demonstrated that intracardiac injection of erythropoietin recruited stem cells, and improved cardiac output and ejection fraction in a rat MI model. Studies in mice by Brunner et al (2009) showed that EPO enhanced migration of stem cells to the ischemic myocardium and that this was mediated through upregulation of SDF-1 expression and the SDF-1/CXCR-4 pathway.…”
Section: Erythropoietin/erythropoietin Receptormentioning
confidence: 99%
“…Administering EPO to rats immediately after coronary occlusion (5000 IU/kg/day for 7 days) reduced cardiomyocyte loss by 50% (Calvillo et al, 2003). Recently, Klopsch et al (2009) have demonstrated that intracardiac injection of erythropoietin recruited stem cells, and improved cardiac output and ejection fraction in a rat MI model. Studies in mice by Brunner et al (2009) showed that EPO enhanced migration of stem cells to the ischemic myocardium and that this was mediated through upregulation of SDF-1 expression and the SDF-1/CXCR-4 pathway.…”
Section: Erythropoietin/erythropoietin Receptormentioning
confidence: 99%
“…Epo promotes proliferation (40,196), inhibits apoptosis (199), and facilitates differentiation of EPCs (200)(201)(202)(203). Furthermore, Epo induces mobilization of EPCs into the circulation (204,205), and their homing (155,206,207). Increased eNOS expression and BH4 biosynthesis has been shown in Epo-treated EPCs and vascular cells ( Fig.…”
Section: Epo In Treatment Of Cardiovascular Diseasesmentioning
confidence: 99%
“…SDF-1a is one of the pivotal signals which can guide mature and immature stem/progenitor directional migration towards the high SDF-1a gradient and protects the stem cell from apoptosis (Jaleel et al 2004). The transient upregulation of SDF-1a level in damaged organ after injury were identified and it could stimulate stem cell mobilization from bone marrow to the injured area (Klopsch et al 2009;Ma et al 2005a). However, SDF-1a could be inactivated and cleaved in a very short half-life (<15 min) by both matrix metalloproteinase-2 (MMP-2) and CD26/dipeptidyl peptidase IV, which are two abundant proteases under inflammatory conditions (De La Luz Sierra et al 2004;McQuibban et al 2001;Peterson et al 2000).…”
Section: Nanocomposite Scaffoldmentioning
confidence: 98%